Factors that influence non-muslims confidence towards islamic banking products / Maizurah Che Mohamad and Nurul Azureen Zulkifli - Che Mohamad, Maizurah; Zulkifli, Nurul Azureen (2014)
Islamic banking is an abstract concept when it was first time establish by Bank Islam Malaysia Berhad. Due to it emergence Islamic banks need to compete with Conventional banks which had operated with a long period time and had strong financial transaction. It not easy to compete with something that had been known for a long period, and had builds a strong customer loyalty through their profit division. However, it is not impossible for Islamic bank to compete and stand in the same level or more strong in term of finance record and customer loyalty from conventional bank. In order to achieve that, Islamic bank have to know how much the level acceptance among the customer and their opinions towards Islamic Bank. The customers must also include Muslim and Non Muslim. Non- Muslims customer can give competitive advantage to Islamic Bank so that it can compete with Conventional Bank. Thus, Islamic Bank need to have a good strategy in orders to win the Non – Muslim heart to increase their confidence to deal with Islamic Banking product and contract. There are some of Non – Muslims thinking that the Islamic banks only to Muslims people and they are not suitable to it. Thus, their confidence levels towards the Islamic banking product are decrease. However, there are some Non – Muslim who believe and have high confidence with Islamic Banking. There are some factors that increase their confidence towards the Islamic banking product. Thus we conduct this research to reveal the factors and explain the factors with the level of confidence